179 Phosphodiesterase-5 inhibition with sildenafil suppresses calcium waves by reducing sarcoplasmic reticulum content. (5th June 2017) - Hutchings, David; Dibb, Katharine; Pearman, Charles; Madders, George; Woods, Lori; Eisner, David; Trafford, Andrew
Abstract : Rationale: Occurrence of diastolic Ca 2+ waves in cardiac myocytes leads to arrhythmias by inducing delayed after-depolarisations. Waves are initiated when sarcoplasmic reticulum (SR) content reaches a critical threshold level. The phosphodiesterase-5 inhibitor sildenafil (Sil) is antiarrhythmic in mammalian myocardial ischaemia models, while Sil reduces Ca 2+ transient amplitude and sarcoplasmic reticulum (SR) Ca 2+ content in rat myocytes. Objective: To determine effects of Sil on propensity to Ca 2?+ waves in the large mammal. Methods: Sheep ventricular myocytes were voltage clamped and intracellular Ca 2+ measured using Fura-2. Cells were paced at 0.5 Hz with depolarisations from −40 mV to+10 mV. When at steady state, waves were induced with 10–15 mM Ca 2+ . Upon regular waving, Sil (1µM) was applied. To determine threshold SR content, caffeine (10 mM) was added immediately following a wave, and both wave and caffeine-induced I NCX integrated. Differences between groups were determined using students paired t tests. Results: Increasing external Ca 2+ to 10–15 mM increased SR content and induced diastolic waves. Sildenafil abolished waves in 9/15 cells. In cells where Sil terminated waves, SR content was reduced below threshold. In addition, Sil treatment was associated with a reduced rate constant of SERCA (kSERCA −66.0±9.9% of control, p<0.005), an initial (first 4 s) increase in sarcolemmal efflux via the I NCX tail current (+142± 36.4%, p<0.01), and reduced sarcolemmal influx via I Ca-L (–30.5±5.6%, p<0.005). In cells continuing to wave in Sil, SR threshold for waves was unchanged (126.9 µmolL -1 ctrl vs 147.2 µmolL -1 Sil, p=0.6). In unstimulated cells spontaneously waving in 10–15 mM Ca² +, sildenafil reduced wave frequency (6.3 waves per 20 s vs 2.7, p<0.005). The protective effect of sildenafil on both wave models was abolished when cells were pre-incubated with the PKG inhibitor, KT5823. Sildenafil suppression of waves was also observed in cells from animals in end-stage heart failure, while Sil suppressed ventricular ectopy and episodes of torsades de pointes in vivo in a sheep model of LQT2. Conclusions: Sildenafil suppresses waves induced by elevated external Ca 2+ via a PKG-dependent mechanism, and mediated by a reduction in SR content, which itself is caused by reduced SERCA function ± reduced I Ca-L . These findings highlight novel antiarrhythmic properties of PDE5 inhibition and translate to suppression of triggered arrhythmias in vivo . Funding: British Heart Foundation.